Applying mathematical analysis in biosciences - Hadjigeorgiou, M.; Gekas, Vassilis (My University, 2010)
Mathematical Modeling in the Biosciences (Food Engineering and Bioengineering) could be enhanced and at the same time facilitated by introducing the method of dimensionless analysis which is widely applied in other branches in Engineering for example in Fluid Dynamics and Chemical Engineering. In the present work dimensionless diagrams have been produced aiming at easily solving Time-Temperature relationship problems and Michaelis-Menten kinetics problems, as well as, bioreactor mass balances, in Biosciences. Also the dimensionless diagram concerning the Balling equation which predicts the alcohol content of the beer has been produced and is presented.
Keywords: Mathematics; Balling equation; Balling equation; Bioreactor design; Dimensionless Michaels-Menten diagram; Dimensionless number; Mass balance; Bioinformatics; Bioreactors; Chemical contamination; Ecosystems; Molecular biology; Molecular structure; Chemical analysis